Open dressing in management of second degree burn in a pediatric burn unit - Ullah, Md Saif; Ferdous, Kazi Md Noor ul; Ara, Sawkat; Bajracharia, Jasmine (Northern International Medical College Journal, 2015)
This study was to evaluate the results of open dressing in management of second degree burn in children. Methods : A retrospective study conducted on children with second degree burn during the period of 42 months from January 2010 to June 2014. Results : 150 patients included in this study. Age range was 1 months 12 days to 11 years 10 months. 68 % patients were within 1-5 years. 70% injured by hot water, 16% by hot liquids, 8.7% by hot cooking related substance and 5.3% due to flame. Only 12% patients showed positive culture of pathogenic organisms. Among them, 4 had a combined growth of Pseudomonas auroginosa and E.coli. 2 (1.3%) patient needed skin grafting. 62% patient stayed in the hospital up to 10 days and only 1 patient stayed 35 days. Mean cost of management per patient was calculated under several categories. Conclusion : Second degree burn can manage by open method effectively and successfully. Regular cleansing of the burnt wound with clean water and application of moist exposed burn ointment (MEBO) can easily be tough to the attendants. Northern International Medical College Journal Vol.6(2) 2015: 73-75